SOSIALISASI MITIGASI PERISTIWA GEMPA BUMI DAN TSUNAMI SERTA AREA EVAKUASI TITIK KUMPUL PADA SEKOLAH SMAN I NANGAPANDA - Lete, Maria Kurniaty; Kaidu, Triapriono; Kabupung, Alfrendo Satriawan; Mado, Theresia Wihelmina (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Natural disasters such as earthquakes and tsunamis can cause death, damage, and property loss for humans. However, this event does not have a bad impact if a building is designed to be earthquake-resistant according to the SNI 1726:2019 standard. SMAN 1 Nangapanda is a school located in the Ende district, this location is close to the coast which has the potential to pose a tsunami hazard; PkM aims to provide education to the school community regarding earthquake disaster mitigation so that disaster victims can be minimised. Implementing this PkM uses methods including material presentations, discussions, and quizzes; and installing evacuation routes at earthquake gathering points in the school environment. The team provided material with a duration of 15 minutes, then gave a quiz and ended with installing an earthquake evacuation route. The results of the PkM running smoothly, and satisfactorily, by the objectives, can be seen from the enthusiasm of the participants in analyzing the animated images in the pamphlets distributed, answering the quiz questions given, activeness in asking and arguing regarding natural disaster mitigation, as well as participation in the activity of installing evacuation route poles gathering point located in the school area. As a follow-up to community service, it is necessary to add simulation activities during the earthquake and tsunami, so that the entire school community can practice these situations.